Career decisions for vocational students through self-efficacy development in the form of electronic publications - Karina, Karina; Irtadji, Moch.; Muslihati, Muslihati; Laksana, Eko Pramudya (Psychology, Evaluation, and Technology in Educational Research, 2021)
Career decisions making is an important thing. Today, many media can be developed to help make the right career decision; one of them is an electronic publication. This research aims to establish an electronic publication (epub) of career decision-making self-efficacy guidance. The development model used was the Borg &Gall model. The initial try out reveals high product validity while the student tries out demonstrates a very accurate, practical, feasible, and fascinating interpretation. The results show that the epub formed career decision-making self-efficacy guidance has fulfilled the theoretical acceptance and practicality aspects; thus, it can be used by the counsellors and students in the career guidance program.